Desarrollo de una guía metodológica para análisis forense en dispositivos móviles con sistema operativo Android (2018)
This project has the main objective to perform forensic analysis on mobile devices with android operating system and document their results to be used in judicial or audit processes, for this reason we have integrated existing tools, a series of phases, scenarios and steps to achieve this objective, which we call a methodological guide. This methodological guide teaches step by step how to extract, identify and analyze the existing information in a mobile device of the operating system android, and presents the results of the analysis in a clear manner so that interested people can use it as elements with probative value